4D-Printed Smart Materials in Clear Aligner Fabrication: A Comprehensive Review - Ebrahimi, Hossein; Khosravi, Setareh (Galen Medical Journal, 2025)
Contemporary dentistry is shifting from passive materials toward biocompatible alternatives with superior mechanical and chemical properties. Smart materials, capable of responding to external stimuli such as temperature, pH, moisture, light, mechanical stress, and electromagnetic or biological signals, are at the forefront of this evolution. Their integration into additive manufacturing has given rise to "4D printing," where printed structures can change over time in response to environmental conditions. In orthodontics, this innovation enables the direct 3D printing of clear aligners, offering precise control over thickness, fit, and design while eliminating thermoforming steps. This results in greater geometric accuracy and workflow efficiency. This review aims to highlight the emerging role of smart materials in clear aligner therapy, focusing on their clinical potential and future applications within the evolving landscape of digital orthodontic